Revised Second Five Year Plan of the North East Frontier Agency. - Planning Commission (Planning Commission, 1955)
The North East Frontier Agency is comprised of some 35,000 square miles in which diverse tribes with an approximate population of 8 lakhs lead an existence varying from self-sufficiency to serious deficiency. The entire area is divided into 6 Divisions. Each Division has 275 villages.
Reference Planning Commission Letter -No. FYII/CDI/17/55 of 14th August. 1955 as Amended by their No FYII/CDI/17/55 of 16th September 1955